Role of joint interactions in upper limb joint movements: a disability simulation study using wearable inertial sensors for 3D motion capture - Nishtha Bhagat; Preeti Raghavan; Vikram Kapila (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Restriction of movement at a joint due to disease or dysfunction can alter the range of motion (ROM) at other joints due to joint interactions. In this paper, we quantify the extent to which joint restrictions impact upper limb joint movements by conducting a disability simulation study that used wearable inertial sensors for three-dimensional (3D) motion capture. Methods We employed the Wearable Inertial Sensors for Exergames (WISE) system for assessing the ROM at the shoulder (flexion–extension, abduction–adduction, and internal–external rotation), elbow (flexion–extension), and forearm (pronation-supination). We recruited 20 healthy individuals to first perform instructed shoulder, elbow, and forearm movements without any external restrictions, and then perform the same movements with restriction braces placed to limit movement at the shoulder, elbow, and forearm, separately, to simulate disability. To quantify the extent to which a restriction at a non-instructed joint affected movement at an instructed joint, we computed average percentage reduction in ROM in the restricted versus unrestricted conditions. Moreover, we performed analysis of variance and post hoc Tukey tests (q statistic) to determine the statistical significance (p < 0.05 denoted using *) of the differences in ROM of an instructed joint in the unrestricted versus restricted conditions. Results Restricting movement at the shoulder led to a large reduction in the average ROM for elbow flexion–extension (21.93%, q = 9.34*) and restricting elbow movement significantly reduced the average ROM for shoulder flexion–extension (17.77%, q = 8.05*), shoulder abduction–adduction (19.80%, q = 7.60*), and forearm pronation-supination (14.04%, q = 4.96*). Finally, restricting the forearm significantly reduced the average ROM for shoulder internal–external rotation (16.71%, q = 3.81*) and elbow flexion–extension (10.01%, q = 4.27*). Conclusions Joint interactions across non-instructed joints can reduce the ROM of instructed movements. Assessment of ROM in the real-world using 3D motion capture, for example using the WISE system, can aid in understanding movement limitations, informing interventions, and monitoring progress with rehabilitation.